Learning English with a native speaker: advantages and disadvantages (Journal of Pedagogical Inventions and Practices, 2023)
This article is dedicated to exploring the issue of learning English with native speakers. The best way to learn a foreign language is to talk to a native speaker. However, do not be misled: not everyone who knows English can give quality knowledge to someone who wants to learn it. As it is known, a native speaker knows the language better, so many people think that this option is definitely more effective. In reality, this is not such a simple matter. There are advantages as well as disadvantages to lessons with a native speaker. In this article, I will try to sort out the pros and cons of learning English with a native speaker